SOFTWARE FOR CALCULATING NODE CONNECTIONS MONOLITHIC REINFORCED CONCRETE BEAMLESS NON-CAPITAL OVERLAP WITH THE COMPOSITE REINFORCED CONCRETE COLUMN - Semko, O.; Dmytrenko, T.; Dmytrenko, A.; Derkach, T. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article touches upon the calculation procedure issue of connection nodes between beamless non-capital monolithic concrete slab and reinforced concrete column to provide bearing capacity in junctions between the slab and the column during design using software The article deals with general calculation principles of connection nodes between beamless non-capital monolithic concrete slab and reinforced concrete column. On the basis of the algorithm to automate the calculation computer program was created in the programming language of Visual Basic for Applications (VBA). The language used for developing applications designed to manipulate databases and to customize the user interface. VBA a structured high-level programming language. In the language of VBA implemented the general principles of object-oriented programming. Keywords: computer technologies, beamless monolithic slab, composite reinforced concrete, shear, algorithm, software.